Rural-Urban Migration for Employment in Kisumu Central Sub-County, Kenya - Onditi, Prisca (JOOUST, 2022)
Rural-Urban Migration for Employment in Kisumu Central Sub-County, Kenya BY Prisca Onditi Unemployment is a global phenomenon that has become a cause of concern at international, regional and national levels as the numbers of migrants surpass the capacity of the urban centers to provide adequate job opportunities. A significant contributor to urban growth and the urbanization process is rural-urban migration. However, the unstable and low-paying jobs in the urban centers compel most migrants to live in informal settlements. The latter is associated with poor living conditions and moral breakdown thus forcing migrants to adopt coping strategies to survive. It is in lieu of this that this study sought to establish the relationship between rural-urban migration and employment in Kisumu Central Sub-County. The specific objectives were to: determine the relationship between socio-demographic characteristics of rural-urban migrants and employment; assess the perception of rural-urban migrants on employment, and to evaluate the coping strategies adopted by rural-urban migrants in Kisumu Central Sub-County. This study was anchored on Harris Todaro’s theory (1969) of migration and the theory of rural urban migration by Papaelias (2013). The study adopted a mixed research methods design. The study used Yamane’s formula to calculate a sample size of 399 from the target population of 174,145 in Kisumu Central Sub County. Simple random sampling was then used to distribute the sample to each ward. Primary data was obtained through questionnaires and key informant interviews while secondary data was acquired through published books, journals, newsletters, internet, theses and dissertations. A total of 321 questionnaires were sufficiently and correctly administered out of a target of 399; making 80.45% response rate. The study established that the relationship between socio-demographic characteristics of rural urban migrants and employment in Kisumu Central Sub-County was negative; with a coefficient of determination (R2 ) of 0.029 and a beta coefficient of 0.074. The study also established that to a large extent; the perceptions of rural-urban migrants on employment in Kisumu Central Sub-County included; higher chances of getting employment in Kisumu City than the locals; migrants with Godfathers and powerful connections have higher chances of getting employment; high expectations of job opportunities; a positive perception on rural-urban migration for employment in Kisumu town; migrants with high level of education have higher chances of getting employed than those with low level of education. Moreover, the study established that the coping strategies adopted by rural-urban migrants in Kisumu Central Sub-County included; engaging in building and construction work, engaging in washing clothes and other odd jobs, sharing rooms and skipping meals. The study recommends that the National and County governments engage in strategic programmes designed to equip the unemployed educated youths with the pre-requisite skills essential to employers in the formal markets. The study also recommends local NGOs to empower migrants on the entrepreneurship culture to help them become economically involved and further create jobs. Finally, the study recommends that government interventions be channelled towards developing infrastructure in the rural areas to help reduce rural urban migration which increases unemployment in the urban areas.
Keywords: Rural-urban migration; Migration; Employment